Analisis Hasil Karya Seni Rupa Dua Dimensi Dengan Pemanfaatan Botol Bekas Sebagai Media Cetak Tinggi - Acnes Ratu Dea; Sugito Sugito (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The purpose of this research is to learn how students use used bottles as high print media to create two-dimensional works of art. Another objective is to find out whether the motifs produced from high prints using used bottles match the motifs on the base of the used bottles and to find out whether the prints match the motifs on the base of the used bottles. This research uses a qualitative descriptive method with a sample of 30 works. The research instrument used an observation sheet on the results of printing practice with used bottles on paper. The analysis technique uses descriptive techniques which are then classified into quantitative data groups. The data obtained will be observed on the results of printed works with predetermined benchmarks and tabulated in tabular form. After being observed, it can be concluded from the results of students' work creating two-dimensional works of art with the utilization of used bottles as high print media with good learning outcomes.